Relationship between soil variables and the plantation site quality in Pinus patula Schiede ex Schltdl. et Cham plantations in Oaxaca, Mexico - García-Aguilar, Juan Ángel (2026)
The site index (SI) is associated with soil properties and the potential for tree growth. Therefore, research was conductedto determine the physical and chemical soil variables most closely related to SI in a Pinus patula Schiede ex Schltdl. et Cham. plantation in the Sierra Norte of Oaxaca, Mexico. Through systematic sampling, 30 circular sites measuring 400 m2 were distributed to compile a forest inventory. In addition, a soil profile was created in the center of each site to collect 60 composite samples at two depths, as well as to measure horizon characteristics. The physical and chemical characteristics of the samples were determined. The sites were classified according to the mathematical expression recommended for the study area. Normality and homogeneity of variance tests were applied to the data. Analyses of variance, correlations, and principal component analysis (PCA) were performed, and finally, the soil variables that were statistically significant were integrated into a multiple regression model. The soil variables that demonstrated the highest adjusted coefficient of determination were as follows: organic horizon thickness (R2 adjusted = 0.77), A horizon thickness (R2 adjusted = 0.46), and organic matter content (R2 adjusted = 0.30). Collectively, these variables explained 78 % of the functional relationship with SI. The soil variables identified in this study can be used by forest managers to select suitable sites for establishing Pinus patula plantations and ensuring high-quality timber yields.